Big girls don't cry: an assessment of Research Units' leadership and gender distribution in Higher Education Institutions - Morais, Ricardo (2022)
Academia is often pointed out as a challenging environment to evolve in, especially for women. Whilst women perform in multidisciplinary settings, studies point out still-existing gender gaps in academia, especially in positions of power. This study looks at decision-making positions in Higher Education Institutions (HEIs), specifically in Portuguese academic research. Furthermore, we seek to understand if research roles are distributed equally gender-wise among cohorts in research units, as well as if deans' genders are a factor of influence in such role attributions. We will look at the research roles in academia, particularly research units fostered by HEIs, to observe gender distribution based on total cohorts. Using univariate and bivariate tests, our research aims to assess gender distribution in leading research roles in public and private institutions. We take the specific case of Portugal; therefore, we cannot extrapolate the results to other countries. However, outcomes point out resisting differences in fields of research and coordination and role distribution among R&D units, as well as in fundamental relations between power positions in academia and research.